On the empresses of the Latin Empire (1204–1261) (5). Marie of Brienne - Pentek, Zdzisław (Balcanica Posnaniensia. Acta et studia, 2024)
Abstract. The article represents the fifth part of the series “On the Empresses of the Latin Empire (1204–1261)”. This one is dedicated to Marie of Brienne, wife of Baldwin II. She was the daughter of John of Brienne and Berengaria of Castile. Marie was betrothed to and then married Baldwin II in 1240 and became empress of the Latin Empire. After the birth of her son Philip (around 1243), she went to France and to the estate of the Courtenay family in Flanders. There she managed the lands on her husband’s behalf. After being exiled to the Latins from Constantinople in 1261, she settled in Naples and probably died there in 1275. Perhaps she was buried in the church of St. Denis in Paris. The author divides her life into four periods that determine her career. The most important periods in her life were the years 1240–1261. The text is based mainly on documentary, sphragistic and sparse chronicle sources. Marie of Brienne has not had an independent biography.